The Princeton Handbook of Multicultural Poetries / - Brogan, Terry V.F. (Princeton University Press, 2021)
Drawn from the acclaimed New Princeton Encyclopedia of Poetry and Poetics, the articles in this concise new reference book provide a complete survey of the poetic history and practice in every major national literature or cultural tradition in the world. As with the parent volume, which has sold over 10,000 copies since it was first published in 1993, the intended audience is general readers, journalists, students, teachers, and researchers. The editor's principle of selection was balance, and his goal was to embrace in a structured and reasoned way the diversity of poetry as it is known across the globe today. In compiling material on 106 cultures in 92 national literatures, the book gives full coverage to Indo-European poetries (all the major Celtic, Slavic, Germanic, and Romance languages, as well as other obscure ones such as Hittite), the ancient middle Eastern poetries (Hebrew, Persian, Sumerian, and Assyro-Babylonian), subcontinental Indian poetries (the widest linguistic diversity), Asian and Pacific poetries (Chinese, Japanese, Korean, Vietnamese, Mongolian, and half a dozen others), continental American poetries (all the modern Western cultures and native Indian in North, Central, and South American regions), and African poetries (ancient and emergent, oral and written).
10.1515/9780691228211
Keywords: Abbreviation.; Aeneid.; Aestheticism.; Allegory.; Alliteration.; Allusion.; Aphorism.; Art for art's sake.; Arthur Rimbaud.; Artifice.; Assonance.; Blank verse.; Caesura.; Charles Baudelaire.; Classicism.; Comparative literature.; Concrete poetry.; Couplet.; Courtly love.; Despair (novel).; Diction.; Didacticism.; Digression.; Dramatic monologue.; Eclogue.; Epic Cycle.; Epic poetry.; Epigram.; Epistle.; Evocation.; Existentialism.; Farce.; Free verse.; G. (novel).; Genre.; Hexameter.; Humour.; Idyll.; Imagery.; Intelligentsia.; Internal rhyme.; Irony.; Jews.; Lament.; Literature.; Long poem.; Lyric poetry.; Lyricism.; Metaphysical poets.; Modernism.; N. (novella).; Narrative poetry.; Narrative.; Neo-romanticism.; Neoclassicism.; New Generation (Malayalam film movement).; Novelist.; Of Modern Poetry.; Oral poetry.; Panegyric.; Parody.; Pessimism.; Petrarch.; Picturesque.; Poet.; Poetic diction.; Poetry.; Political poetry.; Prose poetry.; Prose.; Proverb.; Pseudonym.; Quatrain.; Rainer Maria Rilke.; Rhetoric.; Rhyme scheme.; Rhyme.; Romantic poetry.; Romanticism.; S. (Dorst novel).; Sanskrit.; Satire.; Sensibility.; Sonnet sequence.; Sonnet.; Stanza.; Strophe.; Surrealism.; Symbolism (arts).; T. S. Eliot.; The New Poetry.; The Other Hand.; The Song of Roland.; The Various.; Treatise.; Troubadour.; V.; World War II.; Writer.; Writing.